Empowering Women in Pakistan : Commercial Alternative Dispute Resolution Mechanisms - Merchant, Navin; Ali Khan, Isfandyar (World Bank, Washington, DC, 2012)
An overburdened court system adds to the disadvantages of women in Pakistan. Women entrepreneurs who lack the time and resources to battle a dispute in the courts also run the risk of being victimized for highlighting their problems. Mediation provides a valuable alternative, allowing women and others to settle disputes out of court. As a dispute-settlement mechanism, alternative dispute resolution (ADR) is gaining prominence and increased application in most parts of the world. Its benefits are several. However, for countries where the justice system lacks efficiency, embracing ADR is also difficult. In 2006, International Finance Corporation (IFC) launched an ADR project with a goal of institutionalizing mediation for the first time in Pakistan. Although the project had no provision for separate gender activities, opportunities were created for reaching out to women entrepreneurs and others. This smart lesson relates our experiences and the lessons the authors learned, demonstrating in particular how gender became an integral part of the project and the impact it gained over time.